Chemical Constituents of the Terrestrial Stems of Ephedra sinica and their PPAR-γ Ligand-Binding Activity - Matsuo, Yukiko; Sasaki, Mayu; Fukaya, Haruhiko; Miyake, Katsunori; Takeuchi, Riko; Kumata, Hidetoshi; Mimaki, Yoshihiro (Planta Medica International Open, 2020)
Bioassay-guided fractionation of the MeOH extract of Ephedra sinica terrestrial stems, using a PPAR-γ ligand binding assay, resulted in the isolation of 10 compounds, including one new bisabolane-type sesquiterpenoid (10). The structure of the new compound was determined by extensive spectroscopic analysis, including two-dimensional (2D) NMR. Among the isolated compounds, the sitosterol derivatives (1 and 2), flavonoid glucoside (7), and the new sesquiterpenoid (10), showed significant PPAR-γ ligand-binding activity.
Keywords: Ephedra sinica; Ephedraceae; sesquiterpene; bisabolane; flavonoid; PPAR-γ